TANTANGAN DAN PELUANG HILIRISASI NIKEL BAGI PERUSAHAAN TAMBANG DI INDONESIA - Ahmad, Ardian; Agus Munandar (Accounting Profession Journal (APAJI), 2025)
Indonesia, being the world's largest producer and exporter of nickel, faces challenges in maximizing the added value of this resource. The raw nickel ore export ban policy, which was introduced to support downstreaming, aims to increase state revenue, create jobs, and diversify the economy towards high-tech sectors. The study used both descriptive qualitative approaches and SWOT to evaluate the impact of the policy. It focuses on barriers, opportunities, and implications for the local economy. The results show that the downstream sector has great potential to strengthen Indonesia's position in the world market through the development of nickel-based industries, but requires large investments in technology and infrastructure. The risks faced include international pressure and environmental damage associated with mining activities that require sustainable processing strategies, with the downstream policy Indonesia is expected to become a key player in the international market (electric vehicles and global energy storage technology).